Evaluation of the Pulmonary Tuberculosis Control Program - Muh Khindri Alwi; Asni Hasanuddin; Rony Setianto; Fidrotin Azizah; Belinda Arbitya Dewi; Nilam Fitriani Dai; Ardiansah Hasin; Jurnal Syarif (Jurnal Penelitian Pendidikan IPA, 2023)
Pulmonary Tuberculosis is still a priority health problem in Indonesia, and around 1.5 M people experience TB resistance where the treatment rate is only 38% in 2019 and the global TB treatment rate is only 57% successful, resistant TB costs a lot, is difficult treated so that it becomes a priority for global TB control programs. The high burden of disease and treatment for patients, poor recovery, mortality, and high mortality lead to distress for patients, families, and caregivers. This study aims to determine the success of the program, program achievements include detection rates, conversion rates, cure rates and cross checks, as well as management of human resources and facilities in implementation, as well as obstacles to pulmonary TB disease control programs in Pangkep Regency, the research method used is descriptive to obtain an overview of the P2TB Pulmonary Program in Pangkep Regency. Based on the results of the evaluation of the P2TB program at the community health centers, when viewed from the input aspect, the process is still not in accordance with the applicable requirements and guidelines, the detection of positive smear patients does not reach the target, the cure rate is low below the national target, the error rate is unknown because no cross check is carried out, so it is necessary to have officer training and refreshing courses for laboratory staff, carry out cross checks and cross-program collaboration and PMO guidance, and there is a need for screening activities in areas where there are many sufferers.